Natural products for kidney disease treatment: Focus on targeting mitochondrial dysfunction - Huang, Jiewu; Liang, Ye; Zhou, Lili (Frontiers in Pharmacology, 2023)
The patients with kidney diseases are increasing rapidly all over the world. With the rich abundance of mitochondria, kidney is an organ with a high consumption of energy. Hence, renal failure is highly correlated with the breakup of mitochondrial homeostasis. However, the potential drugs targeting mitochondrial dysfunction are still in mystery. The natural products have the superiorities to explore the potential drugs regulating energy metabolism. However, their roles in targeting mitochondrial dysfunction in kidney diseases have not been extensively reviewed. Herein, we reviewed a series of natural products targeting mitochondrial oxidative stress, mitochondrial biogenesis, mitophagy, and mitochondrial dynamics. We found lots of them with great medicinal values in kidney disease. Our review provides a wide prospect for seeking the effective drugs targeting kidney diseases.